2019
DOI: 10.3390/rel10020114
|View full text |Cite
|
Sign up to set email alerts
|

Family Religiosity, Parental Monitoring, and Emerging Adults’ Sexual Behavior

Abstract: The processes through which families play a role in the religious and sexual socialization of children are varied and complex. Few studies have considered the impact of parental or family religiosity on young people's sexual behaviors, either directly or through influence on adolescents' own religiosity. This study of college students at a large, public university in the mid-Atlantic uses multidimensional measures to examine the relationships among family religiosity, parental monitoring during adolescence, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 67 publications
1
10
0
2
Order By: Relevance
“…In his study, Willard reported that about 18% and 12% of early adolescents engaged in sexting while among late adolescents, 36% of males and 31% of females reportedly sext. A study among Australian adolescents by Scholes-Balog et al (2016), was consistent with earlier studies of Willard (2010) and Klettke et al (2014) Globally, the influence of religion and spirituality on sexuality among adolescents especially with the role played by digital media is still contentious in research (Apostolides, 2017;Quinn & Lewin, 2019). According to Apostolides (2017), religion and spirituality are two different phenomena; spirituality is developed from religious practices and experiences.…”
Section: Introductionsupporting
confidence: 71%
“…In his study, Willard reported that about 18% and 12% of early adolescents engaged in sexting while among late adolescents, 36% of males and 31% of females reportedly sext. A study among Australian adolescents by Scholes-Balog et al (2016), was consistent with earlier studies of Willard (2010) and Klettke et al (2014) Globally, the influence of religion and spirituality on sexuality among adolescents especially with the role played by digital media is still contentious in research (Apostolides, 2017;Quinn & Lewin, 2019). According to Apostolides (2017), religion and spirituality are two different phenomena; spirituality is developed from religious practices and experiences.…”
Section: Introductionsupporting
confidence: 71%
“…The role of family religiosity and students who practice it was also associated with a lower probability of engaging in any sexual activity and a higher probability of condom use. The study pointed out that religious influence positively interferes with university students' sexual behavior (30) .…”
Section: Cultural Values and Lifewaysmentioning
confidence: 99%
“…Instrumen yang digunakan terdiri dari karakteristik sosial-demografi, religiusitas keluarga, parental monitoring, religiusitas remaja, dan perilaku seksual remaja didapatkan bahwa parental monitoring yang didukung dengan religiusitas individu yang tinggi kemungkinan lebih rendah untuk terlibat dalam aktivitas seksual apa pun. (13) Sebuah studi longitudial yang dilakukan menggunakan analisis multivariat didapatkan bahwa remaja pria yang sering berkomunikasi dengan ibu mereka cenderung lebih kecil untuk melakukan perilaku seksual berisiko dibandingkan remaja yang jarang berkomunikasi dengan baik. Selain itu, parental monitoring, disiplin dan komunikasi dengan ayah juga menunjukan hasil yang signifikan bahwa remaja dengan parental monitoring, disiplin dan komunikasi memiliki risiko kecil untuk berprilaku seksual.…”
Section: Seleksi Penelitianunclassified
“…Quinn & Lewin, 2019 (13) Family Religiosity, Parental Monitoring, and Emerging Adults' Sexual Behavior. Religions…”
Section: Cross Sectional 1343mentioning
confidence: 99%
See 1 more Smart Citation